Prevalence of Diabetes Mellitus With Renal Involvement in a Rural Population of Bangladesh - Saha, Ratan Kanti; Roy, Satyajit; Chowdhury, Bidhan Roy; Sarkar, Shoman; Waez, Shakeel; Ahmed, Farid Uddin; Dutta, Pradip Kumar (Journal of Chittagong Medical College Teachers’ Association, 2020)
Background: Population based studies on the prevalence of Diabetes Mellitus (DM) with renal involvement in Bangladesh is limited. It is an obstacle both for the screening program and intervention to prevent this disease. This study was designed to estimate the prevalence of DM with renal involvement among the rural population of Bangladesh. Materials and methods: This cross-sectional study was conducted at selected rural areas in Chattogram district of Bangladesh over the period from January 2014 to December 2014. A total of 2500 individuals age 18 years and above were selected by a multistage sampling method. Diabetic status was assessed by doing Capillary Blood Glucose (CBG) Oral Glucose Tolerance Test (OGTT) and Hemoglobin A1c. Renal function was evaluated by serum creatinine and spot urine dipstick test. Results: Out of 2500 rural residents 557 (22.3%) were found to have DM. Overall 616 (24.6%) subjects had renal involvement and subjects with DM had significantly more renal involvement than the subjects without (36.4% versus 21.3%1). Subjects with DM and renal involvement were significantly older and had lower monthly family income than those without renal involvement. Among 557 subjects with DM, only 41.7% was known to be diabetic. Only 36.3% of the diabetic subjects were aware about their renal involvement. Conclusion: The large proportion of undiagnosed cases of DM indicates the lack of public awareness of diabetes and the shortage of medical facilities. In view of the huge population in Bangladesh, the results of this study emphasize the need to improve the early detection and prevention of diabetes in Bangladesh as a means to prevent the emerging diabetes epidemic. JCMCTA 2019 ; 30 (2) : 57-61